The effect of avatar identity on spontaneous perspective-taking in patients with schizophrenia - Pei Xie; ChaoZheng Huang; XiaoQuan Wang; HanBin Sang; AiBao Zhou (Schizophrenia)
Abstract Controversy exists regarding whether the spontaneity of altercentric intrusion is impaired in patients with schizophrenia during implicit visual perspective-taking tasks. This study explored the characteristics of spontaneous visual perspective-taking in patients with schizophrenia and the effect of an avatar identity on their perspective-taking. We recruited 65 patients with schizophrenia and 65 healthy participants to complete 4 visual perspective-taking experiments for uncued other-avatar and self-avatar tasks and cued other-avatar and self-avatar tasks. In uncued other-avatar experiments, healthy controls showed a significant reduction in accuracy and an increase in response latency when the number of visible discs differed from that seen by the other-avatar (inconsistent condition), indicating altercentric intrusion. However, patients with schizophrenia did not exhibit this effect. In uncued self-avatar experiments, when the avatar was defined as the participant themselves, patients with schizophrenia did not show spontaneous perspective-taking. However, in cued other-avatar experiments, they showed altercentric intrusion in response latency, and in cued self-avatar experiments, they showed altercentric intrusion in accuracy and response latency. These results suggest that patients with schizophrenia have the tendency to spontaneously adopt the perspective of others, which is predicated on their awareness of the existence of perspectives. In addition, the avatar’s identity as a stranger hinders the spontaneous perspective-taking processes in patients with schizophrenia.